Alternations in Physiological and Phytochemical Parameters of German Chamomile (Matricaria chamomilla L.) Varieties in Response to Amino Acid Fertilizer and Plasma Activated-Water Treatments - Malihe Omrani; Mojtaba Ghasemi; Mohammad Modarresi; Ivan Salamon (Horticulturae, 2023)
Plasma-activated water (PAW) is an emerging and promising green technology in agriculture in recent years. This study aimed to examine the influence of the spraying of PAW and amino acid fertilizer concentrations on German chamomile varieties’ physiological, biochemical, and phytochemical characteristics under field conditions. Method: The experiment was performed during 2020–2021 as a factorial using a randomized complete block design with three replications in an arid and semi-arid region east of the Persian Gulf. The factors contained five fertilizer levels (0 (control), 1, 2, 3 mL L−1 amino acid and PAW) and three German chamomile cultivars Bona, Bodegold, and Lianka). Physiological, biochemical, and phytochemical traits such as plant height, fresh and dried flower weight, chlorophyll a, b, carotenoids, CHN elements: N ratio, total protein, amino acid profile, essential oil yield, apigenin content, and major secondary metabolites were examined. Results: The ANOVA indicated that the impact of the cultivar and fertilizer was significant on all physiological, biochemical, and phytochemical studied parameters. The amino acid fertilizer and PAW enhanced physiological features, hydrogen, C: N ratio, essential oil yield, apigenin content, and main phytochemical compositions like chamazulene, and α-bisabolol, but it had no incremental effect on the carbon, nitrogen, and total protein percentage. Conclusion: Findings revealed that applying foliar amino acid fertilizer and PAW treatments improves physiological, biochemical, and phytochemical parameters in German chamomile cultivars under field conditions.